The Efficiency of Financial Performance of Sharia Cooperation through the Data Envelopment Analysis Approach - Pradina Putri, Novia; Sholahuddin, Muhammad; Imronuddin (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The sharia cooperation has an important role in catalyzing a country’s economy. However there is a lot of sharia cooperation institutions that are not performing quite well. This research aims at analyzing the efficiency value of sharia cooperation which is called Baitul Maal Wa Tamwil Surya Madani. The research employs the method of quantitative approaches of Data Envelopment Analysis and the 2019 - 2021 Constant Return to Scale. The secondary data obtained from financial report at three branch offices of BMT Surya Madani in the region of Boyolali. The measurement of efficiency rate uses inputs consisting of third party fund and other operational costs. The result of the research indicates that in 2018 there were two branch offices that experienced inefficiency and the two offices were BMT Surya Madani 2 and BMT Surya Madani 3. From 2019 to 2021 three branch offices of BMT Surya Madani were known to have accomplished efficiency value. It is worth noted that in order to achieve maximum efficiency value there are two approaches that need to be done namely minimizing inputs and maximizing outputs. The result of the research offers valuable understandings to the management of BMT Surya Madani and other sharia cooperation in improving their operational performance and efficiency in the future.